2015
DOI: 10.1590/1516-635x1703371-380
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Combination of Non-Phytate Phosphorus, Phytase and 25-Hydroxycholecalciferol on the Performance and Meat Quality of Broiler Chickens

Abstract: This experiment was conducted to evaluate the combination effect of low dietary non-phytate phosphorus (NPP) concentrations, phytase (PHY) levels, and 25-hydroxycholecalciferol (25-OH-D 3 ) levels on the growth performance and meat quality of broilers. Two levels of NPP, two levels of PHY, and two levels of 25-OH-D 3 resulted in a 2×2×2 factorial arrangements, with eight treatments (TRT). The birds on TRT 1-4 were fed diet 1 (NRC NPP was reduced by 0.1) and the birds on TRT 5-8 were fed with diet 2 (NRC NPP wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Researches showed that dietary NPP supplementation decreased serum malondialdehyde (MDA) levels in laying hens challenged with lipopolysaccharide ( Nie et al., 2018 ) and MDA contents in the muscle of fish, suggesting that NPP reduced lipid and protein oxidation ( Wen et al., 2015 ), which might explain the improvement of meat quality of broilers by NPP. In contrast, Ren et al. (2015) found that meat color (L∗ value, a∗ value, b∗ value) and shear force of the thigh meat or breast muscle were not affected by different levels of NPP.…”
Section: Discussionmentioning
confidence: 71%
“…Researches showed that dietary NPP supplementation decreased serum malondialdehyde (MDA) levels in laying hens challenged with lipopolysaccharide ( Nie et al., 2018 ) and MDA contents in the muscle of fish, suggesting that NPP reduced lipid and protein oxidation ( Wen et al., 2015 ), which might explain the improvement of meat quality of broilers by NPP. In contrast, Ren et al. (2015) found that meat color (L∗ value, a∗ value, b∗ value) and shear force of the thigh meat or breast muscle were not affected by different levels of NPP.…”
Section: Discussionmentioning
confidence: 71%